Acurácia das características definidoras do diagnóstico de enfermagem fadiga em mulheres com câncer de mama em radioterapia - Rocha, Suzy Ramos (2017)
Fatigue is one of the most frequent symptoms in the cancer population, defined as a subjective sense of physical, emotional and cognitive fatigue or exhaustion related to cancer or its treatment, with emphasis on radiotherapy, responsible for the induction of early fatigue in 80% of the Cases. Its complexity is contemplated in the nursing diagnosis, which, if accurate, allows the elaboration of directed interventions. Knowing the degree of incapacity of this symptom, the present study aimed to evaluate the accuracy of the defining characteristics of the nursing diagnosis Fatigue in women with breast cancer in radiotherapy. This is a diagnostic accuracy study of the defining characteristics of the nursing diagnosis Fadiga, performed in the radiotherapy sector of two reference hospitals in oncology located in the city of Fortaleza-CE. The sample consisted of 128 women with breast cancer, over 18 years of age, undergoing radiotherapy. The data collection was performed from May to September 2016, applying a data collection instrument prepared by the author of the study, which contains sociodemographic, clinical and subjective data of the defining characteristics of the nursing diagnosis fatigue. To verify sensitivity and specificity of the defining characteristics of the diagnosis in question, the Latent Class Analysis method was used. Most of the interviewees were brown (56.9%), married or in a stable union (53.1%), from the interior of the state (60.5%), unemployed until the interview date (38%) and with family income between one and two minimum wages (67.7%); staging for primary tumor T2 (45.4%), N0 (42.3%) and M0 (96.9%), with an average of 11.86 months of diagnosis time (DP = 4.33). About 86.2% of the interviewees were submitted to previous chemotherapy and presented an average of 22.38 radiotherapy sessions (DP = 3.54) until the date of the interview. 21.9% of the women with breast cancer in radiotherapy expressed the diagnosis under study. The characteristic that presented greater sensitivity was Capacity impaired to maintain the habitual level of physical activity, while Capacity impaired to maintain the habitual routines and Disinterest as to the environment that presented greater specificity. Identifying the diagnostic profile of this population can contribute to ensure that nursing interventions are guided by accurate diagnoses, thus facilitating the construction of an adequate action plan for this population.